PENGARUH KUALITAS LAYANAN ADMINISTRASI AKADEMIK TERHADAP KEPUASAN MAHASISWA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Ramadhani, Latifa Ramadhani; Syakdanur NAS, Syakdanur NAS; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to determine the influence of the quality of academic administration services to the satisfaction of students of the Faculty of Teacher Training and education (FKIP) Riau University. The population of this research is students of FKIP University of Riau school year 2016-2017 as many as 1,215 students. The sample determination in this study used purposive sampling techniques, where the samples were chosen with certain considerations. Students of FKIP Riau University, 2016-2017, are students who are assessed as having often interacted with the academic administration. From the population above, the 249 samples were set to be considered sufficient to represent the population in the study. Data is collected using a poll of the quality of the academic administration services distributed to respondents. Data analysis uses simple linear regression test data analysis. Based on the results of the research influence the quality of academic administration services on the satisfaction of the University of Riau students is 13.5%, while the remaining 86.5% is influenced by other factors that are not researched in this research such as factors High quality of college performance, facilities and infrastructure, emotional, or cost. It is hoped that the academic administration of FKIP University of Riau can improve the quality of academic service to the students, as this concerns the responsibility as an officer and student assessment of performance.Key Words : Quality of Service, Student Satisfaction.